Further evidence for slow binocular rivalry rate as a trait marker for bipolar disorder. (April 2013) - Vierck, Esther; Porter, Richard J; Luty, Sue E; Moor, Stephanie; Crowe, Marie T; Carter, Janet D; Inder, Maree L; Joyce, Peter R
Objective: Binocular rivalry refers to a situation where contradictory information is presented simultaneously to the same location of each eye. This leads to the alternation of images every few seconds. The rate of alternation between images has been shown to be slower in euthymic participants with bipolar disorder than in healthy controls. The alternation rate is not uniformly slowed in bipolar disorder patients and may be influenced by clinical variables. The present study examined whether bipolar disorder patients have slower alternation rates, examined the influence of depression and explored the role of clinical variables and cognitive functions on alternation rate. Method: Ninety-six patients with bipolar disorder and 24 control participants took part in the study. Current mood status and binocular rivalry performance were analysed with nonparametric tests. A slow and a normal alternation group were created by median split. We subsequently explored the distribution of several clinical variables across these groups. Further, we investigated associations between alternation rate and various cognitive functions, such as visual processing, memory, attention and general motor speed. Results: The median alternation rate was significantly slower for participants with bipolar disorder type I (0.39 Hz) and for participants with bipolar spectrum disorder (0.43 Hz) than for control participants (0.47 Hz). Depression had no effect on alternation rate. There were no differences between participants with bipolar disorder type I and type II and in regard to medication regime and predominance of one rivalry image. There were also no differences in regard to the clinical variables and no significant associations between alternation rate and the cognitive functions explored. Conclusion: We replicated a slowing in alternation rate in some bipolar disorder participants. The alternation rate was not affected by depressed mood or any of the other factors explored, which supports views of binocular rivalry rates as a trait marker in bipolar disorder.